A hybrid fibers based wearable fabric piezoelectric nanogenerator for energy harvesting application. (April 2015) - Zhang, Min; Gao, Tao; Wang, Jianshu; Liao, Jianjun; Qiu, Yingqiang; Yang, Quan; Xue, Hao; Shi, Zhan; Zhao, Yang; Xiong, Zhaoxian; Chen, Lifu
Abstract: Wearable nanogenerators are vital important for wearable devices and portable electronic devices. Here we report a flexible hybrid piezoelectric fiber based two-dimensional fabric nanogenerator which can be promising to be easily integrated with clothing and convert the mechanical energy of human body motion into electric energy. The hybrid piezoelectric fiber comprised aligned BaTiO3 nanowires and PVC polymer. The PVC polymer made the fiber be enough flexible for performing the woven process and the aligned BaTiO3 nanowires enhanced the piezoelectric properties as active materials. The metal copper wires and cotton threads were woven into the fabric to construct the nanogenerator with interdigited electrodes. By attaching the fabric nanogenerator on an elbow pad which was bended by human arms, the nanogenerator can generate 1.9 V output voltage and 24 nA output current and the output are large enough to power a LCD. Graphical abstract: Textual abstract: Wearable nanogenerators are vital important for wearable devices and portable electronic devices. Here we report a flexible hybrid piezoelectric fiber based two-dimensional fabric nanogenerator which can be promising to be easily integrated with clothing and convert the mechanical energy of human body motion into electric energy. The hybrid piezoelectric fiber as active materials comprised aligned BaTiO3 nanowires and PVC polymer. The metal copper wires and cotton threads were woven into the fabric to construct the nanogenerator with interdigited electrodes. By attaching the fabric nanogenerator on an elbow pad which was bended by human arms, the nanogenerator can generate 1.9 V output voltage and 24 nA output current and the output are large enough to power a LCD. Highlights: Hybrid piezoelectric fibers, metal wires and cotton threads were woven into a fabric nanogenerator. The electrodes are naturally integrated in the fabric so that the device looks similar to the conventional fabrics. By attaching the fabric nanogenerator on an elbow pad, the output power of the nanogenerator is large enough to power a LCD.